Comparative risk analysis by VaR: an empirical application to ethical market indices - Derbali, Abdelkader; Saleh, Hany A (Quantitative Economics and Management Studies, 2020)
In recent years, companies' actions towards factors of production have multiplied. The human dimension is increasingly present in decisions and companies feel socially responsible. The sustainability of companies necessarily requires limiting the negative environmental effects because of these production activities. Ethical finance in general, whether Islamic or not, is a growing demand on the part of consumers and states. The aim of this paper is to assess the risk of two ethically responsible indices such as S&P500 Shariah index and S&P500 Environment and Socially Responsible index. In this paper, we will conduct a comparative study of market risk on two ethically responsible indices: the Islamic Index of the Shariah (S&P500 Shariah index) and the S&P500 Environment and Socially Responsible index during the period from 30/09/2010 to 21/09/2018. The evolution of the market will be represented by the general index of the S&P500. To do this, we use different approaches to value at risk such as VaR parametric approach, VaR non-parametric approach and the Theory of Extreme Values approach. Our results show that, on the one hand, the S&P500 Environment and Socially Responsible index is less risky than the S&P500 Shariah index and the S&P500 index. On the other hand, the S&P500 Shariah index is at low risk when yields are extreme. We conclude that the S&P500 Environment and Socially Responsible index is less risky than the Shariah S&P500 Index when you consider that yields are moving under normal market conditions.